2006
DOI: 10.2469/faj.v62.n1.4057
|View full text |Cite
|
Sign up to set email alerts
|

International Evidence on the Payout Ratio, Earnings, Dividends, and Returns

Abstract: • We investigated whether similar findings are evident in 11 major international markets.• We extended the analysis to the relationship between the payout ratio and returns, which we believe to be important because returns are the ultimate focus of portfolio managers and investment strategists. Although the payout ratio has long been of importance to corporate finance researchers (e.g., Lintner 1956), it has been relatively neglected in the asset-pricing and prediction literature (see McManus, ap Gwilym, and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 13 publications
5
25
1
Order By: Relevance
“…Both Zhou and Ruland (2006) and Gwilym et al (2006) supported the findings of Arnot and Asness. Zhou Dhameja ( 1978) in his study tested the dividend behavior oflndian companies by classifying them into size group, industry group, growth group and control group.…”
Section: Arnott and Asness (2003) Based Their Study Onsupporting
confidence: 88%
“…Both Zhou and Ruland (2006) and Gwilym et al (2006) supported the findings of Arnot and Asness. Zhou Dhameja ( 1978) in his study tested the dividend behavior oflndian companies by classifying them into size group, industry group, growth group and control group.…”
Section: Arnott and Asness (2003) Based Their Study Onsupporting
confidence: 88%
“…Arnott and Asness based their study on America stock market (S&P 500) and found that higher aggregate-dividend-payout ratios were associated with higher future earning growth. Both Zhou and Ruland (2006) and Gwilym et al (2006) supported the findings of Arnott and Asness. Zhou and Ruland examined the possible impact of dividend payouts on future earning growth.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 88%
“…Using the changes of EPS as a proxy of one to four years of future earnings growth, the results are represented in Table XIX. As indicated in the table above, the relationship between POR and future earnings growth is negative but insignificant. This means that the POR had no real impact on (Arnott and Asness, 2003;Zhou and Ruland, 2006;Gwilym et al, 2006). To verify this result, we correlated the POR to the future growth on sales per share, and we reached the same conclusion.…”
Section: Dividend Policy and Payout Ratiosupporting
confidence: 66%
“…ap Gwilym et al (2006), using data from 1988 for 6 international equity markets, find that absolute valuation metrics such as earnings and dividend yield can explain a considerable amount of the variation in 5-year returns though the Fed model and other relative yield models are better at forecasting 1-year returns. Table 6 shows the results using the long period of data from January 1952 to June 2011.…”
Section: Fundamental Metrics Versus the 10-monthtrend Following Mamentioning
confidence: 99%
“…Do trend following rules outperform signals based on fundamental metrics such as dividend and earnings' yields (Campbell and Shiller (1988)) the Fed Model (ap Gwilym, Seaton, Suddason and Thomas 2006), the relative yield on bonds and equities (Clare, Thomas and Wickens (1994), and Shiller's cyclically-adjusted price-earnings ratio(CAPE)? We test this by applying the recursive forecast method used by ap Gwilym et al (2006). effectively running a race between the alternative models.…”
Section: Fundamental Metrics Versus the 10-monthtrend Following Mamentioning
confidence: 99%